Thrombotic Thrombocytopenic Purpura as a Model of Accelerated Protein Synthesis - Barnhart, Marion I.; McCutcheon, Sue A.; Riddle, Jeanne M.; Ohorodnik, Julius M. (Thrombosis and Haemostasis, 1964)
Proteins concerned in blood coagulation and clot lysis were studied during a fulminating and fatal case of thrombotic thrombocytopenic purpura.One outstanding feature was the enhanced synthesis of several different plasma proteins. Specific fluorescent antibodies were used to detect cellular synthesis and storage of fibrinogen, prothrombin, albumin, Profibrinolysin and gamma globulin. Most liver cells were actively producing fibrinogen, prothrombin and albumin. Bone marrow eosinophils were synthesizing Profibrinolysin. Peripheral blood eosinophils still contained their packages of Profibrinolysin as if they were transporting this to intravascular thrombi.Another significant finding was that polymorphonuclear leucocytes in the blood were marked with fluorescent antifibrinogen. Breakdown products of fibrin contained in these leucocytes most likely accounted for the attraction of the fluorescent marker. Polymorphonuclear leucocytes may provide an important defense mechanism for individuals in a thrombotic state.